Innovation in the Family Business Succeeding Through Generations - Schmieder, Joe. (A Family Business Publication, 2014)
Schmieder shares a broad range of tools and pathways that family businesses across sectors use to stimulate, execute, measure, and reward innovation. The 50-plus family stories cited in this book will inspire any family enterprise to create a strategy and environment that can stimulate success for many generations to come.